Optimal portfolio execution under cointegrated vector autoregressive systems. (2nd November 2017) - Singh, Arti
Abstract: In this paper, an optimal portfolio execution problem under price model which exhibits cointegration behaviour is proposed. The proposed problem is formulated as a quadratic programming problem. With different statistical procedures and parameter estimation methods, employed on real market financial data, the four portfolios are constructed with which, computational study is performed. It is shown that the trading strategies constructed out of portfolios with cointegrated price dynamics show significant reduction in execution cost.